2016
DOI: 10.17221/216/2015-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of β-d-glucosidase activity of intact cells of two Oenococcus oeni strains with synthetic and natural substrates

Abstract: The β-d-glucosidase (βG) activity of intact cells of Oenococcus oeni SD-2a and 31MBR was assessed with synthetic and natural substrates, also its partial characterisation was investigated. Results showed that intact cells of both strains showed βG activity, SD-2a performing higher than 31MBR, against either synthetic or natural substrate. The high βG activity of SD-2a intact cells under wine-like temperature, pH, ethanol concentration, and glucose concentration could be of great interest for its utilisation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…O. oeni SD-2a, one patent strain screened in China, possesses important oenological characteristics, particularly being able to perform MLF effectively under winery conditions. In previous study, βG activity of O. oeni SD-2a was assessed and partially characterized [11,26,29]. In order to enable a better understanding of the capacity of O. oeni SD-2a to aroma formation during MLF.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…O. oeni SD-2a, one patent strain screened in China, possesses important oenological characteristics, particularly being able to perform MLF effectively under winery conditions. In previous study, βG activity of O. oeni SD-2a was assessed and partially characterized [11,26,29]. In order to enable a better understanding of the capacity of O. oeni SD-2a to aroma formation during MLF.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies had been conducted, providing evidence of the potential βG activity of O. oeni strains for flavor enhancement in wines [7,10,[14][15][16][17][18][19][20][21][22][23][24]. These studies demonstrated that possession of βG activity is widespread and extent of βG activity is strain dependent among O. oeni strains [16,21,25,26], and the enzyme activity is mainly affected by pH, temperature, sugar, and ethanol concentration [15][16][17]19,27,28].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations